ANALISIS SEBARAN DAN PRODUKTIVITAS TANAMAN SAGU DI LAHAN GAMBUT KABUPATEN KEPULAUAN MERANTI - ismayuni, Windia; Sasmita, Lidya; Taryono, Taryono (Universitas Nusa Cendana, 2025)
This study aims to analyze the distribution and productivity of sago plants (Metroxylon sp) on peatlands in the Meranti Islands Regency as an effort to support the green economy and ecosystem conservation. Peatlands have an important ecological function as carbon storage, water regulation, and biodiversity habitats, but their use often causes degradation. Sago, which naturally grows on peatlands, is a strategic local commodity with high economic and ecological value. Research data were sourced from the Central Bureau of Statistics (BPS) in 2022 for land area and sago production, as well as shapefile data on administrative boundaries and peatland distribution from geospatial sources. Quantitative methods were used to calculate sago productivity, while spatial analysis was conducted by overlaying maps of peatlands, rivers, and sago distribution. The results show that the average sago productivity in Meranti is 6.15 tons/ha, which is considered low, Even though districts with large land areas show high potential. The overlay map shows the integration between sago distribution and peatland ecology, as well as the support of small rivers in maintaining moisture. This study emphasizes the need for intensive management, cultivation technology, and land use diversification to increase productivity while preserving ecosystem sustainability, so that sago can become a sustainable flagship commodity in the Meranti Islands.